Studies of self-assembled metal-organic nanostructures and the MBE growth of graphene - Summerfield, Alex (2016)
This thesis discusses the formation of metal-organic and organic structures grown on surfaces using bottom-up self-assembly techniques. Three systems are investigated primarily using scanning probe microscopy techniques.